Three types of end-to-side microvascular anastomosis training models using rat common iliac arteries - Xiao, Zongyu; Wang, Ji; Guo, Jingpeng; Pan, Qi (Frontiers in Surgery, 2023)
Background: Instead of only practicing these perfectly matched end-to-side anastomoses in microsurgical laboratories, we must learn how to perform these so-called “imperfect” end-to-side anastomoses in the laboratory. Methods: Three types of end-to-side microvascular anastomosis using the rat common iliac artery (CIA), one with the proximal end of the CIA to the contralateral side of the CIA, another with distal end of the CIA to contralateral side of the CIA, and the third with the distal end of the CIA to the ipsilateral side of the common iliac vein (CIV), were presented to simulate different end-to-side anastomosis situations in a microsurgical laboratory. Diameters of CIA and CIV, distances between temporary clips, the length of arteriotomy or venotomy, and the distribution of stitches were recorded. The patency rates were evaluated immediately after the anastomosis was completed and 30 min later. After animal euthanasia, the donor vessel was cut close to the anastomotic site, and the orifice size and intimal attachment were evaluated by inspecting them through inside the vessel. Results: The diameters of the CIA and CIV were 0.8-1.2 mm and 1.2-1.5 mm, respectively. The end-to-side microvascular anastomosis arteriotomy or venotomy is approximately 2.00-2.50 mm, the distance between the aneurysm clips on the recipient CIA or CIV is approximately 4.00-7.00 mm and the distance between the corner of the arteriotomy or venotomy and temporary aneurysm clip was 1.00-3.00 mm. Three types of end-to-side anastomosis using the CIA were successfully performed, 100% patency rates were achieved immediately and thirty minutes postoperatively. Good distribution of stitches, wide orifice and intimal attachment were recorded in the study in all groups. Conclusions: Three types of end-to-side anastomosis using rat CIAs could be efficiently used to mimic three different anastomotic situations.